Improved oligonucleotide site-directed mutagenesis using M13 vectors. - Carter, P (1985)
An improved method is described for the construction of mutations in M13 vectors using synthetic oligonucleotides. The DNA is first cloned into a novel M13 vector (based upon M13mp18 or M13mp19), which carries a genetic marker that can be selected against, such as an EcoK or EcoB site, or an amber mutation in an essential phage gene. In this "coupled priming" technique, one primer is used to construct the silent mutation of interest, and a second primer is used to eliminate the selectable marker on the minus strand. After primer extension and ligation, the heteroduplex DNA is transfected into a strain of E. coli which is repair deficient and selects against the plus strand marker. Over 50 mutants have been constructed with this approach, and the yields can be excellent (up to 70%). For the stepwise construction of mutations using separate rounds of mutagenesis, the EcoK and EcoB markers offer a particular advantage over the amber marker. They permit selection in each round, as it is possible to cycle between the two markers. However for construction of multiple mutations over a short region, long synthetic oligonucleotides with multiple mismatches to the template can offer an alternative strategy.